Pediatric Multiple Organ Dysfunction Syndrome: Promising Therapies. Issue 3 (March 2017) - Doctor, Allan; Zimmerman, Jerry; Agus, Michael; Rajasekaran, Surender; Bubeck Wardenburg, Juliane; Fortenberry, James; Zajicek, Anne; Mairson, Emma; Typpo, Katri
Abstract : Objective: To describe the state of the science, identify knowledge gaps, and offer potential future research questions regarding promising therapies for children with multiple organ dysfunction syndrome presented during the Eunice Kennedy Shriver National Institute of Child Health and Human Development Workshop on Pediatric Multiple Organ Dysfunction Syndrome (March 26–27, 2015). Data Sources: Literature review, research data, and expert opinion. Study Selection: Not applicable. Data Extraction: Moderated by an expert from the field, issues relevant to the association of multiple organ dysfunction syndrome with a variety of conditions were presented, discussed, and debated with a focus on identifying knowledge gaps and research priorities. Data Synthesis: Summary of presentations and discussion supported and supplemented by relevant literature. Conclusions: Among critically ill children, multiple organ dysfunction syndrome is relatively common and associated with significant morbidity and mortality. For outcomes to improve, effective therapies aimed at preventing and treating this condition must be discovered and rigorously evaluated. In this article, a number of potential opportunities to enhance current care are highlighted including the need for a better understanding of the pharmacokinetics and pharmacodynamics of medications, the effect of early and optimized nutrition, and the impact of effective glucose control in the setting of multiple organ dysfunction syndrome. Additionally, a handful of the promising therapies either currently being implemented or developed are described. These include extracorporeal therapies, anticytokine therapies, antitoxin treatments, antioxidant approaches, and multiple forms of exogenous steroids. For the field to advance, promising therapies and other therapies must be assessed in rigorous manner and implemented accordingly.